2014
DOI: 10.1099/jmm.0.069427-0
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of PER-1 and diversity of β-lactamases among ceftazidime-resistant Pseudomonas aeruginosa clinical isolates

Abstract: A growing number of b-lactamases have been reported in Pseudomonas aeruginosa clinical isolates. The aim of this study was to investigate the diversity of b-lactamases in the collection of 51 ceftazidime-resistant P. aeruginosa clinical isolates in four hospitals of southern China. Among these isolates, variable degrees of resistance to other b-lactam and non-b-lactam agents were observed. Pulsed-field gel electrophoresis (PFGE) revealed a high degree of clonality with five main genotypes. Of the 51 isolates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…In this study, none of these β-lactamases were found to be enriched in the manure samples; however, several β-lactamases (the Per-1, Per-2, IMP-2 and IMP-5 groups in the arable soil, whereas Per-1, SFO-1, IMP-2 and IMP-5 groups in the pasture soil), which are common in clinical isolates (e.g. Docuquier et al 2003;Qing et al 2014), were observed to be highly enriched in manure-treated soils (Fig. 2), suggesting that the enrichment was likely due to the stimulation of soil indigenous bacteria harboring β-lactamases induced by manure application.…”
Section: Temporal Patterns Of Soil Args and Stimulation Of β-Lactam-rmentioning
confidence: 99%
“…In this study, none of these β-lactamases were found to be enriched in the manure samples; however, several β-lactamases (the Per-1, Per-2, IMP-2 and IMP-5 groups in the arable soil, whereas Per-1, SFO-1, IMP-2 and IMP-5 groups in the pasture soil), which are common in clinical isolates (e.g. Docuquier et al 2003;Qing et al 2014), were observed to be highly enriched in manure-treated soils (Fig. 2), suggesting that the enrichment was likely due to the stimulation of soil indigenous bacteria harboring β-lactamases induced by manure application.…”
Section: Temporal Patterns Of Soil Args and Stimulation Of β-Lactam-rmentioning
confidence: 99%
“…National surveys from Turkey then showed that PER-1-producing P. aeruginosa isolates are widespread in Turkey [2]. PER-1 has been reported in European countries with no geographical border with Turkey, such as Belgium [43], Italy [44], Spain [45], Poland [46], Hungary and Serbia [47] and Tunisia [48] as well as in Asian countries [49,50]. In addition, it was identified in Greece and Iran [51,52] (Table 1).…”
Section: Extended-spectrum ˇ-Lactamases (Esbls)mentioning
confidence: 99%
“…Clinical interest in PER-1 has increased recently due to the detection of this enzyme in multiple Pseudomonas aeruginosa isolates in hospitals in Asia (188), in isolates of Acinetobacter baumannii in Kuwait (189), and in isolates of Providencia stuartii in Tunisia (190).…”
Section: Structure-function Relationships Of Class a Enzymesmentioning
confidence: 99%